Regional Development Information Systems: Them Role in Developing Regions (Information Systems. 23) - Neelameghan, A. (Journal of Information and Knowledge, 1979)
The value of information as resource for national development is emphasised. A structure of Regional Development Information System under the framework of DEVSIS is discussed. The coverage, broad categories of development users, the types of development information needed, the interdisciplinary nature of information, sources of information information generation points, the role of Regional DEVSIS, coordination of the different programmes, factors in inter-regional cooperation, various types of information services, compatibility among norms and devices, agencies promoting cooperation are discussed. The necessary infrastructure is suggested.